‘Stumbling on Civvy Street’: The re-adjustment of white South African war veterans to life in post-war society, 1918-1928 - Delport, Anri (Scientia Militaria - South African Journal of Military Studies, 2016)
The First World War ended in November 1918. As the ink dried on the last treaty in August 1920, the conflict was officially resolved in legal terms. However, this legal finality did not extend to the lives of the soldiers of the war. Their stories of broken lives, shattered marriages, lost careers and opportunities highlighted the fact that the effect of the war lasted well beyond armistice. During the war, some effort had been made by the Union of South Africa to accommodate ex-servicemen, which led to the founding of the office of the Commissioner for Returned Soldiers, the War Special Pensions Act (No. 29 of 1916),[i]the office of the Military Pensions Commissioner, and the Governor-General’s Fund. Through mutual co-operation between these institutions, a variety of schemes were launched to see to the re-integration of the ‘returned soldier’. Such ventures aimed at making ex-servicemen a productive part of the Union workforce, but did little to assuage ex-soldiers’ other needs and future deprivations. In the early 1920s, the atmosphere of mass pride and gratitude to those who had fought for country and empire began to dissipate and a different battle for ex-servicemen began to unfold. Society began to forget, financial aid was reduced, limbless men battled with ideals of masculinity, and the reality of finding and holding down a job was felt more acutely. The former valiant Springboks were being alienated from different spheres of life in the Union. In comparison with other Empire Dominions, South Africa’s loss of life in wartime was relatively light. Yet, for the great majority of soldiers, to have survived was not to have been left unscathed. Some paid their own price with scarred bodies and shattered minds in the form of wounds, amputations and psychological disorders. For the fallen, the war was over. However, for the surviving ex-servicemen, another war began: that of dealing with readjustment to civilian life. The study on which this article is based considered the extent to which men were able, given their altered bodies and minds because of warfare, to reintegrate into post-war society.